1981
DOI: 10.1128/aem.42.5.762-767.1981
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and biophysical alteration of hepatitis B virus antigens by sodium hypochlorite disinfection

Abstract: Sodium hypochlorite (NaOCl) was examined as an effective disinfectant in hepatitis laboratories. Concentrations of NaOCl containing 5,600 ppm (5,600 ,ug/ ml) of available chlorine were found to be effective in destroying the antigenicity of hepatitis B surface antigen (HBsAg) in virion-rich plasma after an exposure time of 1 min or more. In the treatment of protein-deficient solutions containing HBsAg, smaller concentrations of available chlorine (<500 ppm) are equally effective. Neither 17to 25-nm HBsAg parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The mixture was then centrifuged for 3 min at 16 000 rev min −1 . During homogenization, the samples were maintained at 4°C by immersing them in an ice-bath (Sehulster et al 1981;Alverez and O'Brien 1982).…”
Section: Identification and Quantitative Analysis Of Microorganisms Imentioning
confidence: 99%
See 1 more Smart Citation
“…The mixture was then centrifuged for 3 min at 16 000 rev min −1 . During homogenization, the samples were maintained at 4°C by immersing them in an ice-bath (Sehulster et al 1981;Alverez and O'Brien 1982).…”
Section: Identification and Quantitative Analysis Of Microorganisms Imentioning
confidence: 99%
“…Chlorination, ozonation and disinfection using chlorine dioxide have also been used to disinfect waste-water (Geoclifford 1972;Collin and Elleck 1971;Somendu and Ceckler 1974;Alverez and O'Brien 1982). However, the effectiveness of such disinfection is reduced by the presence of suspended solids (Sehulster et al 1981;LeChevallier et al 1981LeChevallier et al , 1984. Under such conditions, ozon-ation always gives low disinfection efficiency unless a high ozone dose is applied.…”
Section: Introductionmentioning
confidence: 99%
“…As for other disinfection methods, such as chlorination, chlorine dioxide, ozone and UV radiation etc., the mutagenic/carcinogenic and toxic disinfection by-products, which are potentially harmful to humans and aquatic organisms, are often accompanied with the disinfection treatment [4]. Moreover, the presence of suspended solids and organic compounds in wastewater often lower disinfection efficiency drastically [5].…”
Section: Introductionmentioning
confidence: 99%
“…While this is the first description of the loss of IgE and IgG binding to antigens fragmented by NaOCl, earlier reports have described immunological effects. Sehulster and colleagues demonstrated that antigenicity of HBsAg was lost after treatment with NaOCl [6]. Our data suggest that antibody binding may be retained in mouse allergen fragments.…”
Section: Discussionmentioning
confidence: 50%